Designing Village Food Security: SWOT–QSPM Strategy for Sumber Harjo Farmers' Group - Wijayanti, Dwi; Putra, Farhan Akmala; Setiadi, Agus (ITScience (Information Technology and Science), 2025)
Strengthening food security at the village level has become a national priority, with farmer groups (Gapoktan) serving as key grassroots institutions. However, the organizational and strategic capacity of many Gapoktan remains underdeveloped, especially in rural areas such as Mulyoagung Village, Bojonegoro. This study addresses the need to design targeted strategies for empowering Gapoktan Sumber Harjo to support food security programs funded through the Village Fund. This study uses a quantitative strategic model to formulate strategic priorities for developing Gapoktan Sumber Harjo. The research applied a descriptive approach using Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Strengths-Weaknesses-Opportunities-Threats (SWOT) matrix, and Quantitative Strategic Planning Matrix (QSPM). Data were collected through interviews, documentation, and expert judgment scoring. The IFE results indicated a score of 2.6608, suggesting moderately strong internal conditions. The EFE score reached 3.0090, showing that external conditions are highly supportive, especially through the Village Fund policy and local government programs. QSPM analysis identified the most attractive strategies to generate leadership and capacity-building in digital skills. This study concludes that Gapoktan’s internal reinforcement must precede any external partnership or digitalization effort. Strategic development based on empirical scoring ensures policy alignment and community participation. These findings will inform local governments and grassroots institutions in prioritizing sustainable, data-driven agricultural strategies.